2016
DOI: 10.1111/ggi.12717
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between built environment attributes and physical function in Japanese community‐dwelling older adults

Abstract: The present study suggests that, although there are some sex differences, low population density, land use mix, and fewer daily life-related destinations, community centers, medical facilities and recreational facilities are negative determinants of physical function. Geriatr Gerontol Int 2017; 17: 382-390.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 53 publications
(75 reference statements)
3
48
0
1
Order By: Relevance
“…A cross-sectional survey in 2010-2012 also suggests that there were poor performance of STS and TUG in elderly people of age 65 to 86 years. In our study, higher values of FTSTS and TUG test suggested an increased risk of fall 22 and decline in functional mobility.…”
Section: Discussionsupporting
confidence: 60%
“…A cross-sectional survey in 2010-2012 also suggests that there were poor performance of STS and TUG in elderly people of age 65 to 86 years. In our study, higher values of FTSTS and TUG test suggested an increased risk of fall 22 and decline in functional mobility.…”
Section: Discussionsupporting
confidence: 60%
“…As in the empirical studies of the United States, Canada, and Germany [43][44][45][46][47][48], do people who live in areas with a higher level of walkability walk and bike more than those who live in areas with a lower level of walkability in Seoul, Korea? There are some previous studies from Asian countries similar to this topic, however, most focused on either promoting physical activity for older adults [52][53][54][55], or using survey/interview-based measurement of walkable environments [56,57]. Most importantly, there has been little research on the association between walkable environments and active commuting.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report to examine walkability in a sample of workers whose residential location is more geographically dispersed than those in community-based samples. The present study is also unique in terms of the urban-suburban setting, as epidemiologic studies are often conducted in rural settings in Japan ( Eshak et al, 2017 ; Soma et al, 2017 ). One previous study in Japan did not find any significant associations between residential neighborhood GIS-measured walkability and leisure-time physical activity (walking and exercise combined) in women, but identified a marginal relationship in men ( Hanibuchi et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%